PSYCHOLOGICAL ADAPTATION OF THE KLATEN COMMUNITY TO THE VALUES OF THE NYADRAN TRADITION IN THE MODERN ERA: Adaptasi Psikologis Masyarakat Klaten Terhadap Nilai-Nilai Tradisi Nyadran Di Era Modern - Marcelius Sampe Tondok; Yunita (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2026)
This study aims to examine the forms of psychological adaptation among the people of Klaten toward the Nyadran tradition amid the currents of modernization. Employing a descriptive qualitative approach, data were collected through in-depth interviews with four informants representing different generations and professions, and subsequently analyzed using thematic analysis as proposed by Miles and Huberman (1994). The findings indicate that the Nyadran tradition continues to play a significant role in shaping cultural identity and resilience among the Klaten community. Three main themes emerged: (1) emotional and spiritual attachment to the tradition, (2) the roles of social structure and gender in cultural preservation, and (3) the tension between traditional values and modern lifestyles. The older generation tends to maintain conventional practices with strong emotional commitment, whereas the younger generation demonstrates reinterpretation of cultural values through digital media as a form of contextual adaptation. These findings underscore that the psychological adaptation process within the Klaten community reflects cultural resilience (Panter-Brick & Eggerman, 2021), defined as the capacity to preserve the essence of cultural values amidst social change. This study contributes to the enrichment of cultural psychology literature by highlighting intergenerational dynamics in the preservation of local traditions, as well as the importance of intergenerational narrative transmission in sustaining cultural relevance in the future.